Educação Financeira Crítica: um olhar em desfavor ao neoliberalismo e políticas mercadológicas - Sousa, Ivan Bezerra de (2024)
With the implementation of the National Common Core Curriculum (BNCC) in Brazilian schools in 2018, financial education began to be emphasized more in some textbooks, curriculi, classrooms and teachers’ continuing professional development. While important, its implementation has been the topic of much debate due to the strong link between the subjects of financial education and of marketing strategies, a subject already present in education in general. In light of this debate, this project explores the conjoining of three axes of study: field of sociology, in which neoliberalism and its impacts on society is discussed; financial education, in which the ways financial education has been taught in schools is emphasized; and math education, in which the lens of Critical Mathematics Education is applied to the discussion of the relationship between sociology and math education. Using the connections between these axes of study as its starting point, the following general objective is proposed: to develop alternative understandings of financial education through dialogues carried out by an expansive educational process with teachers of different curricular subjects that focus on financial education in the context of neoliberal ideologies. In order to obtain the results of this research, the Financial Education in Debate Series was created. It guides an educational process with teachers of different curricular subjects and was implemented in a few Brazilian states. The results from the participants' dialogic interactions became the main source of the ideas discussed in this thesis. The Financial Education in Debate Series is organized in three modules. The first module uses themes, chosen by the researcher, intended to present, in a general way, reflections and debates on the implementation of financial education in the current neoliberal environment. In contrast to the first module, in the second module the participants are responsible for using critical thinking to debate themes of their interest involving financial education. The third module uses activities, elaborated and re-elaborated, in the line of critical financial education (CFE), which gave rise to this study´s educational product. This research is qualitative in nature, as it interprets and analyzes the results of the implementation of the three aforementioned moduless. The data collection instruments used were audio and video recordings, chats on Google Meets, participants' written records in Google Classrooms, photographic records and questionnaires. Based on the results of the field research, a detailed analysis was made of how the participants understood this research proposal. The following guiding question was used: How do discursive interactions in the Financial Education in Debate Series influence teachers' thinking about financial education in a neoliberal context? Do their discussions reveal an approach to financial education that is increasingly critical of the traditional neoliberal approach, one that could be called critical financial education? Statements that emerged from participant interactions during each module were described using Critical Discourse Analysis (CDA), based on the ideas of Fairclough and other scholars. This study highlights an understanding among the participants of the harmful effects of the neoliberal attack on contemporary society, brings new perspectives to financial education, and emphasizes the resistance needed during these dark, capitalistic times to form trailblazers in the struggle for social justice.